Desenvolvimento de biocompósitos PLA/PBS/Biocargas para impressão 3d de scaffolds para engenharia de tecidos ósseos - Lima, Luana Caroline Góis (Universidade Federal de São Carlos, 2025)
The increasing demand for bone implants to treat diseases or injuries has driven the search for new approaches capable of providing functional substitutes. These solutions, known as scaffolds, aim to address tissue scarcity and adapt in a personalized manner to the individual needs of each patient. To be effective, these scaffolds must exhibit biocompatibility, controlled bioresorbability, mechanical stability, and the ability to promote cell adhesion, proliferation, and differentiation. Therefore, this study aimed to develop biocomposite scaffolds composed of a blend of poly(lactic acid) (PLA) and poly(butylene succinate) (PBS) in a 75:25 (% w/w) ratio, incorporating two biofillers: β-tricalcium phosphate (TCP) or bone powder (BP). The biocomposites were produced by melt mixing in an internal mixer and subsequently subjected to rheological and thermal characterizations before being used to manufacture 3D-printed scaffolds. The incorporation of biofillers resulted in a small reduction in the viscosity and thermal stability of the blend, indicating possible polymer degradation induced by the addition of these biofillers. Despite this, the 3D printing process demonstrated excellent morphological reproducibility, resulting in scaffolds with adequate structural integrity for bone repair applications. Mechanical tests revealed that the addition of biofillers (10% and 20% w/w) did not significantly enhance mechanical performance and ensured compatibility with natural bone tissue. In vitro cytotoxicity tests, performed with mouse pre-osteoblastic cells (MC3T3-E1), confirmed the biocompatibility of the scaffolds, evidenced by good cell adhesion and the absence of toxic effects. The results indicate that PLA/PBS (75/25) scaffolds with TCP and BP have great potential for applications in bone tissue engineering, as they combine processability, mechanical stability, and bioactivity.
Development of PLA/PBS/Biofillers biocomposites for 3D printing of scaffolding for bone tissue engineering
Keywords: Poli (ácido láctico); Poli (butileno succinato); Engenharia de tecidos ósseos; Manufatura aditiva; Biocompósitos; Poly (lactic acid); Poly (butylene succinate); Bone tissue engineering; Additive manufacturing; Biocomposite; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 3. Saúde e Bem-Estar